Analysis of geometrical tomographic parameters of furcation lesions in periodontitis patients - Gonçalves, Bianca Costa [UNESP]; Costa, Andre Luiz Ferreira; Correa, Raquel [UNESP]; Andere, Naira Maria Rebelatto Bechara [UNESP]; Ogawa, Celso Massahiro; Santamaria, Mauro Pedrine [UNESP]; de Castro Lopes, Sérgio Lucio Pereira [UNESP] (Elsevier, 2021)
Cone beam computed tomography; Digital volume tomography; Furcation defect; Furcation involvement; Periodontal regeneration; Periodontal disease.

Objectives: This study was aimed to investigate the relationship between geometric parameters of furcation lesions - maximum area of lesion opening (MALO), angle formed between the roots (ABR), lesion volume (LV) and presence and height of infra-osseous defects (IOD) - and the success of therapy with enamel matrix derivative proteins (EMD) in patients with grade C periodontitis, using cone-beam computed tomography (CBCT). Methods: The study consisted of two groups of patients with grade C periodontitis: control (surgery) (n = 17) and test (surgery + EMD) (n = 17). Images parameters on CBCT were recorded using OnDemand3D and ITK-SNAP software. Results: Pearson's correlation coefficient demonstrated that only IOD was statistically significant in the probing depth PD (P = 0.01), with a moderate positive correlation (R = 0.59). MALO was found to be statistically significant (P = 0.03) in the test group (surgery + EMD), with moderate negative correlation (R = -0.5). Conclusion: The presence of infra-osseous defects and height were relevant in relation to the success of the type of treatment addressed in this study.
Keywords: Cone beam computed tomography; Digital volume tomography; Furcation defect; Furcation involvement; Periodontal disease; Periodontal regeneration